2016
DOI: 10.1002/gps.4481
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of visual perception and reasoning ability in Alzheimer's disease: correlation between Raven's Colored Progressive Matrices test and 123I‐IMP SPECT imaging results

Abstract: Our findings suggest that deteriorations of specific brain regions are associated with dysfunction of visual perception and reasoning ability in AD. RCPM is another informative assessment scale of cognition for use in patients with AD. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
1
1
2
1
Order By: Relevance
“…In addition, we demonstrated an association between connectivity impairment in prefrontal regions and visuospatial/logical reasoning performance, as measured by Ravens' Colored Progressive Matrices score. The association between visuospatial/logical reasoning and dorsolateral prefrontal cortex has been shown by several fMRI studies in healthy subjects (Krawczyk, Michelle McClelland, & Donovan, 2011;Kroger et al, 2002) and in patients with neurodegenerative dementias (Yoshida et al, 2017). Our results provide further evidence for an association between executive dysfunction and frontal connectivity impairment in DLB, consistent with previous hypotheses (Lee et al, 2010;Sourty et al, 2016).…”
Section: Neuropsychological Deficitssupporting
confidence: 91%
“…In addition, we demonstrated an association between connectivity impairment in prefrontal regions and visuospatial/logical reasoning performance, as measured by Ravens' Colored Progressive Matrices score. The association between visuospatial/logical reasoning and dorsolateral prefrontal cortex has been shown by several fMRI studies in healthy subjects (Krawczyk, Michelle McClelland, & Donovan, 2011;Kroger et al, 2002) and in patients with neurodegenerative dementias (Yoshida et al, 2017). Our results provide further evidence for an association between executive dysfunction and frontal connectivity impairment in DLB, consistent with previous hypotheses (Lee et al, 2010;Sourty et al, 2016).…”
Section: Neuropsychological Deficitssupporting
confidence: 91%
“…In AD, predominant left hemisphere hypoperfusion/hypometabolism (including in the LP region) as indexed by SPECT/positron emission tomography was reported to be positively correlated with verbal deficits such as verbal and logical memory, word‐pair learning, and reading 45,46 . In contrast, predominant right hemisphere hypoperfusion (including in the IPL) was reported to be positively correlated with scores on neuropsychological tests of visual memory and visuospatial cognition in MCI 47,48 . However, in the present study, we observed no significant differences in neuropsychological test results between the LLP hypoperfusion (+) and RLP hypoperfusion (+) groups.…”
Section: Discussioncontrasting
confidence: 88%
“…45,46 In contrast, predominant right hemisphere hypoperfusion (including in the IPL) was reported to be positively correlated with scores on neuropsychological tests of visual memory and visuospatial cognition in MCI. 47,48 However, in the present study, we observed no significant differences in neuropsychological test results between the LLP hypoperfusion (+) and RLP hypoperfusion (+) groups. These negative findings may be partially attributed to the insensitivity of the neuropsychological tests used in this study to determine LLP and RLP differences.…”
Section: Discussioncontrasting
confidence: 82%
“…RPM is a sensitive measure for cognitive sequelae of stroke and dementia [25]. Iodoamphetamine single-photon emission computed tomography (I-IMP SPECT) studies have shown that RPM scores are positively correlated with regional cerebral blood flow in various lobes [26]. Perhaps the impaired cerebral vascular regulation seen in those with low haemoglobin may explain this reduction in RPM scores.…”
Section: Discussionmentioning
confidence: 99%